(untitled) (Boletin Médico de Postgrado, 2023)
Following the COVID-19 pandemic, a new entity has emerged, the "post-COVID" syndrome, with multiple manifestations among which cardiovascular symptoms are mentioned. The aim of this study was to determine the frequency of cardiovascular dysautonomia in post-COVID-19 patients who attended the IPSTAUCLA clinic between July and December 2021. A cross-sectional descriptive study was conducted whose population consisted of 48 post-COVID-19 patients; those with a history of dysautonomia or current use of vasodilator drugs, β-blockers, nonpyrimidine calcium channel blockers, and centrally acting sympatholytics were excluded. A structured questionnaire was administered that included questions on orthostatic intolerance and syncope (COMPASS survey), physical examination, and the modified RINES-VALCARDI and active standing tests. Cardiovascular dysautonomia was observed in 31% of post-COVID-19 patients according to the presence of alterations in at least one of the clinical diagnostic parameters; this was less frequent in those with more time elapsed since the active infection. Fifty-eight percent were female and 29% were between 50 and 59 years of age. Cardiovascular dysautonomia was present in 13% and 19% of patients with moderate and severe infection.